SUBJECTIVE WELL-BEING AND HEALTHY BEHAVIOR OF ELDERLY WITH DEMENTIA ALZHEIMER’S (A PHENOMENOLOGICAL STUDY) - Pariama, Aprillia Mauren; Ranimpi, Yulius Yusak; Setiawan, Adi (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2020)
Background: Dementia is a syndrome caused by decreased cognitive function due to aging, genetics, vascular disease and low physical and cognitive activities. Alzheimer's is the most common cause of dementia. Despite experiencing holistic changes in their lives, elderly with dementia Alzheimer's are entitled to well-being. Measurement of Subjective Well-being (SWB) is used to determine the well-being state of elderlies.Objective: The purpose of this study is to analyze the expression of Subjective well-being (SWB) and the healthy behavior of elderlies with dementia Alzheimer's.Methods: This study uses a qualitative phenomenological approach with a descriptive hermeneutics type. The data collection was done by in-depth interview techniques with the type of auto-anamnesis, observed, and family statements. The data analysis process was carried out in 3 stages (Verbatim, initial and focused coding, determination of categories were made in the form of themes). Data validity test used data triangulation techniques.Results: Participants in this study are 3 elderlies age 75 and 76 years who had mild dementia Alzheimer's. This condition affects participants ability in expressing their SWB and health behavior that are described in physical disorders, life satisfaction, satisfaction with important domains, positive influence, behavior change, treatment-seeking, and cognitive failure.Conclusion: Reported high subjective well-being is closely related to the low level of unpleasant emotions during their life journey. Healthy behavior is strongly influenced by knowledge, demographic factors, personal goals and values, social influence, and access to health services. Two participants managed to express SWB and healthy behaviors better than one participant.